Pengaruh latihan self-talk terhadap kepercayaan diri saat kumite pada atlet INKAI sumbawa barat dalam kejuaraan bupati cup lombok tengah - Zahrul Muhajir; Muhammad Salah; Fadli Zainuddin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study investigates the impact of self-talk training on the self-confidence of karate athletes from INKAI Sumbawa Barat during kumite competitions at the 2025 Bupati Cup IV in Lombok Tengah, Indonesia. Self-talk—defined as internal verbalization aimed at enhancing psychological resilience—has been recognized in sports psychology as a technique to regulate anxiety, boost focus, and foster motivational drive. Employing a one-group pretest-posttest experimental design, the research involved 20 karate athletes who participated in a structured self-talk intervention across 12 sessions. Data on self-confidence levels were collected using validated and reliable Likert-scale questionnaires and analyzed through statistical methods including normality testing, homogeneity testing, and paired-sample t-tests. Results revealed a statistically significant increase in athletes’ self-confidence following the self-talk intervention (p<0.001), confirming the effectiveness of this mental strategy in high-pressure competitive settings. The findings contribute to the theoretical understanding of psychological skills training in sports and offer practical recommendations for coaches and athletes seeking to enhance mental preparedness and performance in kumite.